LOW BACK PAIN: Literature Review - Shafia, Anindya; Ismunandar, Helmi; Putri, Giska Tri; Saftarina, Fitria (CV. Jasa Sukses Abadi, 2025)
Low back pain (LBP) is one of the most common musculoskeletal problems and a leading cause of disability and global productivity loss. This condition can be either acute or chronic and is caused by various factors, including mechanical, radicular, and nociplastic components. The complexity of its etiology and the variability of treatment responses necessitate a comprehensive and multidimensional approach. This study is a literature review that examines scientific articles obtained from databases such as PubMed, Scopus, and Google Scholar. The articles reviewed were published between 2015-2025 and discussed aspects of definition, epidemiology, classification, diagnosis, and pharmacological and non-pharmacological management of LBP. The review found that LBP has a high global prevalence, particularly among the productive age group and the elderly. Risk factors include biomechanical, psychosocial, and lifestyle aspects. Management of LBP involves pharmacological treatments (NSAIDs, tramadol, duloxetine) and non-pharmacological approaches (physical exercise, education, multidisciplinary rehabilitation). LBP is a complex public health issue with significant economic and social burdens. Effective management strategies require a biopsychosocial approach, appropriate use of screening tools, and multifactorial interventions tailored to the type and phase of pain. Prevention through education and physical activity has also proven effective in reducing the risk of LBP occurrence.